The Use of Both Therapeutic and Prophylactic Vaccines in the Therapy of Papillomavirus Disease - Garbuglia, Anna Rosa; Lapa, Daniele; Sias, Catia; Capobianchi, Maria Rosaria; Del Porto, Paola (Frontiers in Immunology, 2020)
Human papillomavirus (HPV) is the most common sexually transmitted virus. High Risk (HR) HPV types (HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 59) are considered the main aetiological agents of genital tract cancers such as cervical, vulvar, vaginal, penile anal cancers and of a subset of head and neck cancers. Three prophylactic HPV vaccine are available:2-,4-, and 9-valent vaccines. The bivalent vaccine is against HPV16 and HP18 types, the 4-valent is against HPV6, 11, 16, and 18, and the 9-valent is against HPV6, 11, 16, 18, 31, 33 ,45, 52, and 58. All vaccines are based on recombinant DNA technology and they are prepared from purified L1 protein that self-assembles to form HPV type specific empty shells (virus-like particles, VLPs). These vaccines are highly immunogenic and induce specific antibodies. The therapeutic vaccines differ from prophylactic vaccines since they are aimed to generate cell-mediated immunity against transformed cells rather than neutralizing antibodies. Among HPV proteins, E6 and E7 oncoproteins are considered near ideal targets for the immunotherapy of cervical cancer since these proteins are essential for the onset and evolution of malignancy and are constitutively expressed in both premalignant and invasive lesions. Several strategies have been investigated for HPV therapeutic vaccines designed to enhance CD4 and CD8 T cell responses including genetic vaccines (DNA/RNA/virus/bacterial), protein-/ peptide- or dendritic cell (DC)-based. However, no vaccine has yet been licensed for therapeutic use. Several studies suggested that the administration of prophylactic vaccines immediately after the surgical treatment of CIN2+ cervical lesions could be considered as adjuvant to prevent reactivation or reinfection, other studies described the relevance of prophylactic vaccines in the management of genital warts. This review summarises the leading features of therapeutic vaccines, which mainly target the early oncoproteins E6 and E7, and prophylactic vaccines based on the L1 capsid protein. By analyzing the specific immunogenic properties of the two types of vaccines, we will try to explain why / how the prophylactic vaccine can be effective in treating HPV-related lesions or in preventing the development of HPV-related relapse.